One bear at bedtime : a counting book - Inkpen, Mick. (Boston : Little, Brown, 1988)
Introduces the numbers one through ten as a little boy describes all the animals he needs to help him get ready for bed.
2.0
K-3
Keywords: Counting; Bedtime -- Fiction; Counting; Bedtime -- Fiction